Lean-Agile Adaptations in Clinical Laboratory Accredited ISO 15189 - Carlos Vilaplana Pérez; Gloria Soria Guerrero; Federico Garriga Garzón; Angel Salas Garcia (Applied Sciences, 2015)
It’s introduced Lean techniques in a Clinical Laboratory to improve the operability and the efficiency in continuous processes of analysis, failsafe systems, analysis of areas of value pursuit of zero defects and reduction of waste, and it promote continuous improvement in presented difficulties in adapting to the changing needs of the healthcare environment. Whereas it is necessary to incorporate certification and accreditation, note that the adaptability of the clinical laboratory to the changing needs of physicians in obtaining analytical information is reduced. The application of an agile methodology on analytical systems can provide a line of work that allows the incorporation of planning short work cycles on equips quickly with operational autonomy on the basis of demand and respecting the accreditation requirements and flexibility to ensure adequate performance as the intercomparison of results from the different units analytics, analytical quality and turnaround times. Between 2012 and 2014, a process of analysis and improvement was applied to circuits, a 5 s system, transportation of samples, inventory of reactive and samples, motion of personal and samples, reductions of waiting and delays, overproduction, over processing, and defects of results and reports. At last it seems necessary to apply the Agile methodology to adapt to the evolving necessities in time and the different origins of the samples. It’s have used modular systems where the modules of this study are programmed with immunoassay techniques and it has reduced the operative modules depending on the required activity, ensuring the goals of turnaround times, analytic quality, service, health care continuity, and keeping up with the ISO 15189 accreditation requirements. The results of applying the concept of Lean-Agile to a modular system allows us to reduce the associated costs to the seasonal variation of the health care demand and to adapt the system to the changes on the pattern of analytic demand. The savings obtained are two laboratory technicians for a month and those derived from deactivating a complete modular section consisting of three analysts. Average turnaround time (TAT) of 99.5% from the analyzed parameters has been kept equal to the one obtained in common conditions with a p < 0.01. The laboratory has maintained the quality goals measured in analytical variability. Prior to that, it most objectified the inter-comparability of the results among the used channels.